Maternal exposure to air pollutants and birth weight in Tehran, Iran - Nakhjirgan, Pegah (J Environ Health Sci Eng, 2019)
BACKGROUND: Air pollution can cause various health outcomes, especially in susceptible groups including pregnant women. Low birth weight (LBW) is among the adverse birth outcomes and is one of the main causes of infant mortality. The aim of this study was to assess the association between air pollutants and LBW in Tehran, Iran. METHODS: In this case-control study, 2144 babies born in three hospitals of Tehran (Iran) during 2011 to 2012 whose mothers were the residents of this city in last 5 years were considered. Of these, 468 infants with birth weight < 2500 g and 1676 with birth weight ≥ 2500 g were regarded as case and control groups, respectively. Gestational age was also considered for definition of cases (small for gestational age (SGA)) and controls (appropriate for gestational age). Land use regression models were used to assess exposure to particulate matter ≤10 μm in aerodynamic diameter (PM(10)), sulfur dioxide (SO(2)), nitrogen dioxide (NO(2)) and volatile organic compounds (benzene, toluene, ethylbenzene, o-xylene, m-xylene, p-xylene (BTEX), and total BTEX) during pregnancy. Logistic regression model was applied to assess the association between air pollutants and LBW. RESULTS: The concentrations of air pollutants were very high but similar in cases and controls. After adjustment for potential confounding variables, no statistically significant association was observed between air pollutants and LBW. The adjusted odds ratios (95% confidence interval) for PM(10), SO(2), and benzene were 0.999 (0.994–1.005), 0.998 (0.993–1.003), and 0.980 (0.901–1.067), respectively. CONCLUSIONS: No association was found between LBW and air pollutants. Further studies with more rigorous designs and access to more comprehensive information are suggested to assess the effect of other air pollutants, such as CO, O(3), PM(2.5), ultrafine particles, and oxidative potential of particles on birth outcomes.